Fluorosulfate-containing pyrazole heterocycles as selective BuChE inhibitors: structure-activity relationship and biological evaluation for the treatment of Alzheimer's disease. (31st December 2022) - Li, Huan-Huan; Wu, Chengyao; Zhang, Shi-Long; Yang, Jian-Guo; Qin, Hua-Li; Tang, Wenjian
Abstract: Novel scaffolds are expected to treat Alzheimer's disease, pyrazole-5-fluorosulfates were found as selective BuChE inhibitors. Compounds K1–K26 were assayed for ChE inhibitory activity, amongst them, compound K3 showed potent BuChE and h BuChE inhibition (IC50 = 0.79 μM and 6.59 μM). SAR analysis showed that 1-, 3-, 4-subtituent and 5-fluorosulfate of pyrazole ring affected BuChE inhibitory activity. Molecular docking showed that the fluorosulfate increased the binding affinity of h BuChE through π-sulphur interaction. Compound K3 was a reversible, mixed and non-competitive BuChE inhibitor ( K i = 0.77 μM) and showed remarkable neuroprotection, safe toxicological profile and BBB penetration. In vivo behavioural study showed that K3 treatment improved the A β 1 − 42 -induced cognitive impairment, and significantly prevented the effects of A β 1 − 42 toxicity. Therefore, selective BuChE inhibitor K3 has potential to be further developed as AD therapeutics.